SUBTITUSI TEPUNG TEMULAWAK (Curcuma xanthorhiza sp) PADA PAKAN DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN DAN SINTASAN BENIH IKAN NILA (Oreochromis niloticus) - Rahmi Rahmi; Nur Insana Salam; Nur Qodri (Universitas Muhammadiyah Makassar, 2016)
The purpose of this study to determine the effect of ginger powder in the feed with different doses of the survival and growth of tilapia fish (Oreochromis Niloticus). The method used is tilapia fish obtained from Fish Seed Center (BBI) is natural. Seed fish used as many as 10 heads/container research. Total container study 12 units with a capacity of each container of 20 liters of water. Research container filled with water of 10 liters. The treatments tested was the administration of different doses of ginger powder in feed tilapia fish. In this study, there were 4 treatment, the dosage of 2.5% (treatment A), the dose of 5% (treatment B), the dose of 7.5% (treatment C), without the provision of ginger powder (treatment D). Research carried out for 6 weeks showed that the growth and survival rate of tilapia fish highest in treatment B (ginger 5%) with an absolute growth of 2.68 gr, 0.0638 g daily growth, and survival rate of 100%.